Poly(3, 4-ethylenedioxythiophene):sulfonated acetone-formaldehyde: preparation, characterization and performance as a hole injection material. Issue 34 (17th August 2016) - Yu, Wei; Xie, Xiang; Li, Yuda; Li, Yuan; Chen, Runfeng; Qiu, Xueqing; Huang, Wei
Abstract : Poly(3, 4-ethylenedioxythiophene):sulfonated acetone formaldehyde was prepared, which shows superior performance in a blue PHOLED device as the hole injection layer. Abstract : Initially, sulfonated acetone-formaldehyde condensate (SAF) was widely applied as a second generation water reducing agent in the construction industry owing to its excellent properties, simple preparation and low cost. Considering the much lower cost of SAF compared with poly(styrene sulfonate) (PSS), a new water dispersed poly(3, 4-ethylenedioxythiophene):sulfonated acetone-formaldehyde (PEDOT:SAF) is prepared using SAF as a dopant of PEDOT for the first time. Significantly, many interesting properties, including low acidity, high work function, conductivity and surface thiophene/sulfonate ratio ( R T/S ), good dispersion stability, film-forming property and hydrophilia, were found in PEDOT:SAF. Furthermore, in order to evaluate its application prospect, a blue phosphorescent organic light-emitting diode (PHOLED) was fabricated using PEDOT:SAF as the hole injection layer (HIL). The device showed superior performance with the very low turn-on voltage ( V on ) of 3.4 V and high maximum efficiency of 16.4% EQE, 30.1 cd A −1 CE and 19.4 lm W −1 PE. These results are better than those of traditional PEDOT:PSS-based devices with the same device configuration. Our research displays the great prospect in the use of SAF as an alternative dopant of PEDOT and provides a promising strategy to design water-soluble non-aromatic dopants of conductive polymers.